Tingkat Pengetahuan Tentang Vitamin C Di Apotek Al Fayadh Farma 1 Bantul Yogyakarta - Ria Rizka Santika; Fitria Dhirisma (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Vitamins are substances needed by the body because they have important functions for the body, vitamin C also has a role in the body's metabolic activities. Vitamin C deficiency can cause deficiencies in various diseases, such as mouth ulcers, anemia, dry skin and gingivitis. The aim of this research was to determine the level of knowledge regarding the use of vitamin C at the Al-Fayadh Potorono Pharmacy, Bantul. This research uses descriptive observational methods and uses prospective research methods. The sample used is 110 respondents. Data collection used a closed questionnaire. Data analysis used the Guttman scale where correct answers were given a score of 1 and wrong answers were given a score of 0, and categorized by percentage into 3 categories, namely good 76-100%, sufficient 56-75%, and less <56%. Based on the research results, it shows that the level of patient knowledge regarding the use of vitamin C is in the good category, 67 respondents (61%), sufficient category is 38 respondents (34%),and less than 5 respondents (5%). So it can be concluded that the level of knowledge of patients at the Al Fayadh Farma Pharmacy regarding the use of Vitamin C is good